VD_FINDINFO HC / 2013 / 763 vom 27. November 2013 - VD Tribunal cantonal (2013)
RADIATION DU RÔLE, MESURE DE CONTRAINTEDROIT DES ÉTRANGERS | 15 LVLEtr, 25 al. 1 LVLEtr, 30 LVLEtr, 31 LVLEtr, 242 CPC (CH)